MODELLING PEDESTRIAN'S DECISION TO CROSS IN MIDBLOCK OF URBAN AREA - WICAKSANA - NIM : 25017007, RIAN
High population density in urban area, poor transportation system, and the disobedience of road users toward the existing traffic lead to the condition where traffic accidents easily occur, including those that involves pedestrian. The traffic accidents where pedestrians get involved are usually caused by the pedestrian itself does not cross on the crossing facility. To comprehend this kind of condition, this research used ordinal logistic regression as a descriptive model. Based on the result collected, the main factors affecting jaywalking behavior are gap size, time pressure, appearance of another crossing pedestrian, crossing experience, and pedestrian group are the main factors of pedestrian’s decision to cross the road. However, in two-lane one-way road, the crossing experience of pedestrian is not affecting their decision to cross. On divided four-lane two-way road, pedestrian’s decision to cross is not affected significantly by time pressure and pedestrian group. The most significant factor of pedestrian’s decision to cross the road is gap size. All of these factors cannot be intervened so that the pedestrians’decision to cross can be put under control. Moreover, in terms of the element of the street itself, namely the number of direction of traffic and existence of traffic island can significantly affect pedestrian’s decision to cross the road. Conversely, in this research, the number of lanes is not significantly affecting pedestrian’s decision to cross the road. Having compared the model with binomial logistic regression and multiple linear regression, then it was found that all of these models cannot properly describe the pedestrian’s decision to cross the road.